Manufacturing in real time managers, engineers and an age of smart machines - Frontini, Gian F. (Butterworth-Heinemann, 2003)
The development of self-operating machines is the foundation of modern manufacturing. This current manufacturing environment is based on automation and smart machines that have the ability to make things with a level of accuracy and consistency that humans cannot match. In order to maximize efficiency, engineers and managers need to change their outlooks, processes and strategies and as a result, adopt new methods and management systems. The authors demonstrate what is needed by first presenting a brief history of manufacturing and the changes we have already seen and then make their way into the current manufacturing environment. Topics covered include supply chain management, product streams, the role of automation in the supply chain, the relationships between machines and people in automated product streams (looking at what machines do best and what humans do best), variation and quality control, statistical process control, the flow of information in a supply chain and how all of these elements are effected by new technologies and need to be changed to allow for maximum efficiency as we move more toward automation in factories. *Discover the impact of new technologies on the future shape on the manufacturing industry *Excellent examples used throughout to demonstrate each idea and process *Includes a CD with lectures, slides, tutorials, dynamic models and much more!